HUBUNGAN KESELAMATAN DAN KESEHATAN KERJA DENGAN KINERJA KARYAWAN BAGIAN MINING PRODUCTIONS PT. THIESS CONTRACTORS SANGATTA PROJECT - Herman; Amransyah; Meita Sondang Riski (Tinta Nusantara 2018 Vol.1, 2020)
The purpose of this study was to analyze the relationship between occupational safety (X1), occupational health (X2) and employee performance (Y) in the Mining Production division of PT. Thiess Contractors Sangatta Project. This study uses correlation analysis, which is the analysis used to determine the relationship between variable X and variable Y. The questionnaire data was filled out by 67 respondents and processed using the SPSS version 21 application program. The results of the study show the relationship between the variables, either partially or jointly, on employee performance. The relationship that is explained by the variables of work safety (X1), occupational health (X2) together with the performance of employees (Y) in the Mining Production division of PT Thiess is 88.6%, the rest is explained by other variables that have not been included in the research model